No Veteran Left Behind? Perspectives on VTC Eligibility Criteria for Justice-Involved Veterans in Multiple Jurisdictions Across the United States - Hummer, Don (Victims & offenders, 2024)
The explosive growth of veterans treatment courts (VTCs) in the United States has raised questions concerning which justice-involved veterans (JIV) are eligible and ultimately selected for participation. For instance, should VTCs be more inclusive in their selection processes, and is it possible to do so within existing court parameters? Using data from 145 interviews of team members working in 20 VTCs across the country, this study explores the perceptions of those personnel on a range of factors impacting eligibility determinations of JIV. These include the decision-making processes of VTC teams, determinations of the nexus between a veteran’s military service and their offending behavior, and the capacity of jurisdictions to provide treatment and services to all JIV, either through Veterans Affairs programs or community providers. Findings illustrate the variability of VTCs nationwide and suggest that specific midcourse alterations are necessary to fulfill stated court missions.